(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The author analysis the connection between patriotism and social studies education. The author provides two lesson plans (one primary and one secondary) that look at three professional athletes’ racialized and political experiences. This article includes two example lesson plans to aid instructors in directing students toward a critical understanding of patriotism via fostering informed action within and outside the classroom, based on fundamentals of critical racial media literacy and conceptual understandings of critical patriotism.